VILNIUS ACADEMICAL COMMUNITY AND ITS LIBRARY IN THE FIRST HALF OF THE 19TH CENTURY: THE IMPACT OF THE IMPERIAL GOVERNMENT - KRAKYTĖ, ASTA (Knygotyra, 2015)
The subject of the research depending to the history of the librarianship of Lithuania is directly connected to the political and social situation in the state in the beginning of the 19th century and the dispersion of the ideas of the Enlightenment all over Europe. The article explores various historical sources (library manuscript catalogues, book proveniences, orders of tsar, correspondence of Vilnius University with the imperial administration) to investigate the period from the time Lithuania was annexed by Russia and Vilnius Jesuit Academy was reorganised to the imperial university in 1803 by tsar Alexander I up to the date Vilnius University activity was interrupted by the orders of tsar Nicholas I in 1832, which coincided with the noticeable alteration in the educational system, new subordination and points of the academical community, changed structure, financing, replenishment methods and finally the partition of Vilnius University library. The main notice of the article is to refer to a description of influence of the imperial government to the library and Vilnius University community as the most educated part of Lithuanian society of this epoch for compare appropriate characteristics with and the substantiality at the end of the 18th century when the local community and its library was under leadership of the order of Jesuits (dissolved in Europe in 1773) to examine existing positive estimations of the traditional historiography on the issue. The research covers some directions of Vilnius academical community activity under changing conditions related to the replenishing of the library (using traditional and the new forms), management, catalogues rewriting, imperial censorship, propaganda and the painful partition of book collection confiscated from the closed Vilnius University and lifted to Kiev and Charkov universities, the gymnasium of Orsha (now – Mogilev district, Belarus) and to other libraries of the empire of Russia. After the detailed analysis of significant historical documents kept in Lithuanian State Historical Archive and Vilnius University Library it is recovered the negative impact of the Russian imperial Government authority both for the local community and its library as well. It is disclosed that next to particular progressive changes in the field of the library financing and replenishing of the book collection by European science papers and popular periodicals, such as “Journal des sçavans” by D. De Sallo (Paris, 1665–1797), “Allgemaine Literatur Zeitung” by F. J. J. Bertuch (Halle, 1804–1849), “Bibliotheca italiana, o sia Giornale di letteratura scienze ed arti compilato da vari letterati” (Milano, 1816–1840), “The Repository of Arts, Literature, Commerce, Manufacturers, Fashions and Politics” by R. Ackermann (London, 1809–1829), “The Repertory of patent inventions, and other discoveries and improvements in arts, manufactures, and agriculture” (London, 1825–1862), “The Annals, Edinbourgh Medical und Surgical Journal” (Edinbourgh, 1805–1855, etc.). The Russian imperial authorities forwarded significant loses of values, changed essential points of members of the local academical community, limitated the access of works of modern European authors (Voltaire, C. F. de Volney, P. H. Holbach, D. Diderot, etc.) and influenced the straitening of dispersion of ideas of the Enlightenment, influenced the obsolescence of Vilnius University library and the noticeable interruption of development of the traditional European librarianship in Vil-nius social environment.